'HAVE YOU FELT ANGRY LATELY?': A NOTE ON UNFAIR WAGE PERCEPTIONS AND THE NEGATIVE EMOTION OF ANGER. (3rd March 2016) - Pfeifer, Christian
ABSTRACT: The author analyses the nexus between unfair wage perceptions of workers and the frequency of the negative emotion of anger. For this purpose, German household panel data for the years 2007, 2009, 2011 and 2013 are used. Angry feelings in the last four weeks have occurred significantly more frequently for workers who perceive their wage as unfair, whereas the own absolute hourly wage is not significantly correlated with the frequency of having felt angry. The results further indicate that workers have felt more often angry if working hours are larger; but the economic significance seems rather small compared to unfair wage perceptions.